Assessment and comparison of multivariate process capability indices in ceramic industry (Journal of Mechanical Engineering, 2009)
Process capability indices are intended to provide a single-number assessment of the consistency of a manufacturing process relative to the engineering specification limits on quality characteristics. In many industrial instances product quality depends on a multitude of dependent characteristics and as a consequence, attention on capability indices shifts from univariate domain to multivariate domain. In this paper five different multivariate methodologies are used for measuring and comparing capability of a ceramic table-ware manufacturing process. Based on their multivariate process capability index values and expected rejection rate, the result shows that Castagliola's index is the best and followed by Chen, Taam, Shahriari and Braun respectively in this case. Keywords: Process capability indices, Multivariate process capability indices, Multivariate Capability Plot, Multivariate control chart doi:10.3329/jme.v39i1.1829 Journal of Mechanical Engineering, vol. ME39, No. 1, June 2008 18-25